Arabic Computer Syllabus Model Based On 21-st Century Skills - Ihwan Rahman Bahtiar; Chakam Failasuf; Siti Jubaidah (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
Globalization and the acceleration of technology in the 21st century create a new paradigm in education. Teachers are not only required to transfer knowledge but also to equip their students with various 21st-century skills. This study aims to produce a syllabus for Arabic Computer courses based on 21st-century skills at the Arabic Language Education Study Program, Faculty of Language and Arts, State University of Jakarta. This development research uses the Successive Approximation Models 1 (SAM1) model, combined with the Merdeka Belajar Kampus Merdeka syllabus model. This study used data collection methods through questionnaires for expert team assessment and interviews for one-on-one trials. Data analysis used the Guttman scale, namely a score of 1 for the answer